Molecular characterisation and function analysis of the rice OsDUF872 family - Lihua Li; Miaomiao Lv; Jiyao Li; Taozhi Ye; Xia Li; Xiang He; Songhao Rong; Yilun Dong; Ying Guan; Lu Zhao; Hui Li; Jinghong Xu; et al. (Biotechnology & Biotechnological Equipment, 2018)
With the advance of sequencing technology, the number of sequenced plant genomes has been rapidly increasing. However, many plant proteins in public databases are recognised as proteins with domains of unknown function (DUF). DUF872 is such a protein family that consists of plant proteins with unknown function. In this study, we analysed three DUF872 members (OsDUF872.1, OsDUF872.1 and OsDUF872.3) in rice Nipponbare with three distinct motifs. Real-time polymerase chain reaction showed that the expression patterns of the three corresponding OsDUF872 protein-encoding genes varied in 15 different rice tissues. The expression of OsDUF872.2 was significantly (P < 0.01) upregulated under salt, cold and heat stress conditions. Overexpression of OsDUF872.2 in Escherichia coli significantly improved the resistance to heat. These results improve our understanding of these poorly-studied proteins and provide information for future studies on other proteins of unknown function.